The strength of the polymer composite (fiberglass) with interlaminar shear - A.A. Boldyreva; Y.A. Yarunicheva; A. V. Dernakova; I.I. Ivashov (Инженерно-строительный журнал, 2016)
Multilayered fiberglasses – the first almost mastered fibrous composites. Ultimate strength of an interlaminar shear is one of the key parameters necessary for calculation of constuctions made of laminated composites.. This paper presents test of multilayer fiberglass exemplars for ultimate strength at an interlaminar shear carried out by method short beam shear test, also research of influence of distance between pillars on a value of ultimate strength of an interlaminar shear is presented. Tests were carried out by Instron 5965 with reference equipment for a three-point bend and a digital USB microscope of DigiMicro 2.0 for tracking and fixation of the moment of emergence in exemplars of the interlaminar shear cracks.